2013
DOI: 10.5435/jaaos-21-12-727
|View full text |Cite
|
Sign up to set email alerts
|

Early Weight Bearing After Lower Extremity Fractures in Adults

Abstract: Weight-bearing protocols should optimize fracture healing while avoiding fracture displacement or implant failure. Biomechanical and animal studies indicate that early loading is beneficial, but high-quality clinical studies comparing weight-bearing protocols after lower extremity fractures are not universally available. For certain fracture patterns, well-designed trials suggest that patients with normal protective sensation can safely bear weight sooner than most protocols permit. Several randomized, control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 40 publications
1
70
1
2
Order By: Relevance
“…8 Previous studies have examined the incidence of VTE in body regions rather than with specific fracture locations. A prospective randomized controlled trial by Goel et al showed no significant difference in the incidence of DVT with chemical prophylaxis or placebo in fractures below the knee, although tibia plateau fractures showed a trend towards increased risk of VTE.…”
Section: Discussionmentioning
confidence: 99%
“…8 Previous studies have examined the incidence of VTE in body regions rather than with specific fracture locations. A prospective randomized controlled trial by Goel et al showed no significant difference in the incidence of DVT with chemical prophylaxis or placebo in fractures below the knee, although tibia plateau fractures showed a trend towards increased risk of VTE.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on postoperative weight bearing are scarce, but is has been shown that patients with early weight bearing return to work earlier than patients with no weight bearing (Simanski et al 2006, Kubiak et al 2013, Black et al 2014. According to biomechanical studies, axial loading stabilizes the ankle joint and prevents translational talar movement as well as external talar rotation (Sasse et al 1999).…”
Section: Postoperative Immobilization and Weight Bearingmentioning
confidence: 99%
“…According to biomechanical studies, axial loading stabilizes the ankle joint and prevents translational talar movement as well as external talar rotation (Sasse et al 1999). Therefore, early weight bearing should be encouraged following operative stabilization of ankle fractures (Starkweather et al 2012, Kubiak et al 2013, Black et al 2014. However, in obese and diabetic patients a longer period of non-or partial weight bearing is recommended, as premature weight bearing is the greatest contributing factor to a loss of reduction in this patient population (Bibbo et al 2001, Wukich and Kline 2008, Rizvi et al 2010, Chaudhry and Egol 2011.…”
Section: Postoperative Immobilization and Weight Bearingmentioning
confidence: 99%
“…[4][5][6][7] It could be said that fractures of the legs may be more disabling to the geriatric patient than hip fractures, due to the fact that rehabilitation of such ''below-the-hip'' fractures often requires weight-bearing restriction on the injured lower extremity (unlike after hip fracture repair); patients therefore require assistive devices, such as a walker or crutches, for ambulation. 8,9 Since many geriatric patients may lack sufficient upper body strength for routine use of walker or crutches, their mobility may be dramatically curtailed by a weight-bearing restriction on 1 or both legs. 8 Fractures below the hip are common in patients with osteoporosis and may represent an important and growing problem for the elderly population.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Since many geriatric patients may lack sufficient upper body strength for routine use of walker or crutches, their mobility may be dramatically curtailed by a weight-bearing restriction on 1 or both legs. 8 Fractures below the hip are common in patients with osteoporosis and may represent an important and growing problem for the elderly population.…”
Section: Introductionmentioning
confidence: 99%